KOMUNIKASI TERAPEUTIK DALAM PERSPEKTIF ISLAM - Sinaulan, Ramlani Lina (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2016)
Therapeutic communication is a mutual interaction between nurses and patients in the communication process that aims to solve the problems facing the patients. This article explores the therapeutic communication from the Islamic perspective. Therapeutic communication will be more meaningful when a nurse interacts directly with the patient, especially through strengthening of the spiritual elements that will be a positive suggestion for recovery. In this case, the nurse made himself or herself therapeutic through the optimal use of various communication techniques with the aim of leading the patient’s behavior toward a positive direction through strengthening the religious values.